DEVIATION ANALYSIS OF L*a*b* VALUE ON MILK PACKAGING MOLDS - Sahid Noor Wahid; Septia Ardiani; Anton Hadiwibowo (Kreator, 2022)
The color deviation that occurs during the printing process is one of the problems often encountered in the graphics. This is very detrimental in terms of cost, time and energy. To know the color deviation, you can measure the L*a*b* value of the print. The offset printing process is used in this deviation analysis of L*a*b* value. When the technical specifications relate to paper, ink, machines, techkon measuring instruments and milk packaging products The machine used is the Heidelberg Speedmaster machine where there are four stages of operation, namely the preparation of machine, machine setting, ACC color and production in many quantities. The instrument used to measure the deviation of L*a*b* value or ΔE value of the milk packaging is Techkon. The value of L*a*b* for special colors as a reference is taken from the color gamut, i.e. at minimum L*: 20.21, a*: 7.09, b*: -40.19, standard L*: 18.69, a*: 9.77, b*: -42.63, maximum L *: 18.41, a*: 11.16, b*: -43.65, and the maximum value of ΔE* ab is 2.50. The factors that cause deviation are the thickness of the ink layer and the color reflection from the paper surface. Giving an ink layer less / thin, the resulting color tends to match the reflection of the paper surface, giving a thicker ink layer can cause the print to set off and the color to deviate from the color range.Keywords— Deviation, L*a*b* value, Milk Packaging